Sickle Erythrocytes and Platelets Augment Lung Leukotriene Synthesis with Downregulation of Anti‐Inflammatory Proteins: Relevance in the Pathology of the Acute Chest Syndrome. (1st September 2014) - Opene, Michael; Kurantsin‐Mills, Joseph; Husain, Sumair; Ibe, Basil O.
Abstract : Initiation, progression, and resolution of vaso‐occlusive pain episodes in sickle cell disease (SCD) have been recognized as reperfusion injury, which provokes an inflammatory response in the pulmonary circulation. Some 5‐lipoxygenase (5‐lox) metabolites are potent vasoconstrictors in the pulmonary circulation. We studied stimulation of production of the inflammatory eicosanoids leukotrienes (LTs) and prostaglandin E2 (PGE2 ) by isolated rat lungs perfused with sickle (HbSS) erythrocytes. Our hypothesis is that HbSS erythrocytes produce more LTs than normal (HbAA) erythrocytes, which can induce vaso‐occlusive episodes in SCD patients. Lung perfusates were collected at specific time points and purified by high‐pressure liquid chromatography, and LTC4 and PGE2 contents were measured by enzyme‐linked immunosorbent assay (ELISA). Rat lung explants were also cultured with purified HbAA and HbSS peptides, and 5‐lox, cyclooxygenase 1/2, and platelet‐activating factor receptor (PAFR) proteins were measured by Western blotting, while prostacyclin and LTs produced by cultured lung explants were measured by ELISA. Lung weight gain and blood gas data were not different among the groups. HbSS‐perfused lungs produced more LTC4 and PGE2 than HbAA‐perfused lungs: 10.40 ± 0.62 versus 0.92 ± 0.2 ng/g dry lung weight (mean ± SEM; P = 0.0001) for LTC4 . Inclusion of autologous platelets (platelet‐rich plasma) elevated LTC4 production to 12.6 ± 0.96 and 7 ± 0.60 ng/g dry lung weight in HbSS and HbAA perfusates, respectively. HbSS lungs also expressed more 5‐lox and PAFR. The data suggest that HbSS erythrocytes and activated platelets in patient's pulmonary microcirculation will enhance the synthesis and release of the proinflammatory mediators LTC4 and PGE2, both of which may contribute to onset of the acute chest syndrome in SCD.